German translation, cultural adaptation and testing of the Person‐centred Practice Inventory - Staff (PCPI‐S) - Maya L. D. Weis; Martin Wallner; Sabine Köck‐Hódi; Christiane Hildebrandt; Brendan McCormack; Hanna Mayer (Wiley, 2020)
Abstract Aim The aim of this study was to translate and culturally adapt the PCPI‐S into German and to eventually test its psychometric properties in long‐term care settings. Background Person‐centred practice has been widely adopted internationally as a best‐practice model in nursing and health care. To ensure a sustainable implementation of this practice and to successively promote it, person‐centred practice should be evaluated on a regular basis. The Person‐centred Practice Inventory-Staff (PCPI‐S), which is based on McCormack & McCance's Person‐centred Practice Framework, is a new instrument for this purpose by assessing perceptions of person‐centredness among healthcare staff. Design A two‐phase research design was used involving the translation and cultural adaption of the PCPI‐S from English to German (PCPI‐S‐G; Phase 1) and a quantitative cross‐sectional survey (Phase 2). Methods Construct validity was evaluated using confirmatory factor analysis (CFA), and internal consistency was calculated using Cronbach's α. Results Phase 1 was conducted using an internationally recommended checklist for translations and cultural adaptations. In Phase 2, the PCPI‐S‐G was tested in 15 residential care homes in Austria with a sample of 255 staff members. The CFA showed good construct validity and supported the theoretical framework. The internal consistency for the three constructs of the PCPI‐S was excellent, revealing Cronbach's α‐scores from 0.902-0.941.